On the kinetics of anodic processes at oxidation of aqueous solutions of dimethyl sulfoxide - Abdulhadi, Saif Ali; Tulska, Alona Gennadiivna; Bayrachnyi, Volodymyr; Sinkevich, Irina Valeriivna (Національний технічний університет "Харківський політехнічний інститут", 2021)
Dimethyl sulfoxide is a feedstock for a large number of organic substances syntheses. Nowadays research is considerably focused on the production of general products of dimethyl sulfoxide oxidation – dimethyl sulfone and methane sulfonic acid. Dimethyl sulfone is well–known as a food supplement for the treating and strengthening of human joints and ligaments. dimethyl sulfone is basically synthesized by oxidation of dimethyl sulfoxide in hot 30 % hydrogen peroxide in glacial acetic acid. Synthesis is accompanied by significant losses of hydrogen peroxide, the target product has to be significantly purified. It becomes possible to control the synthesis of pure dimethyl sulfone and methane sulfonic acid when using the electrochemical method of oxidation of dimethyl sulfoxide in its aqueous solution with chemically resistant anode and high overvoltage of oxygen reaction Controlled synthesis is relevant because sulfur tends to change the oxidation rate. Study of kinetics of anodic processes at platinum electrode was performed in the dimethyl sulfoxide concentration range about 1.0…4.0 mol·dm⁻³. Current raise was observed at potentials that are more positive than 1.3…1.4V. This potential range corresponds to oxygen release. Dissolved sulfuric acid (0.2 mol·dm⁻³) was added in order to inhibit the oxygen release and achieve the potential for the formation of peroxide radicals in aqueous solutions of dimethyl sulfoxide. It is known that sulfate ions are adsorbed on the surface of the platinum anode, displacing molecules of protonated water. This allows to shift the potentials and increase of the electrolysis current in 0.2 mol·dm⁻³ H₂SO₄ to 1.7…1.9V. It indicates the processes of formation of peroxide radicals on the surface of the platinum anode. Further shift of the anode potential into more positive area than 2.00…2.05V leads to a rapid increase in current density. At such potentials, dimethyl sulfoxide and dimethyl sulfone are oxidized to methane sulfonic acid with a parallel oxygen and hydrogen peroxide release. Current–voltage study has shown that the oxidation of dimethyl sulfoxide in aqueous solutions runs through the formation of dimethyl sulfone. When conducting electrochemical synthesis with control of the anode potential, it is possible to produce dimethyl sulfone without further oxidation to methane sulfonic acid. The addition of 0.2 mol·dm⁻³ H₂SO₄ to aqueous dimethyl sulfoxide solutions inhibits oxygen release and intensifies oxidation of dipole dimethyl sulfoxide molecules adsorbed on the platinum surface. The influence of adsorption processes on the kinetics of anode processes at the platinum anode in aqueous solutions of dimethyl sulfoxide at high anode potentials has been studied.

Диметилсульфоксид є сировиною у великій кількості синтезів органічних речовин. Значний інтерес являє одержання цільових продуктів окислення диметилсульфоксиду – диметилсульфону та метан сульфокислоти. Диметилсульфон поширений як харчова домішка, що призначена для лікування і укріплення суставів и звязок людини. За звичай, диметилсульфон синтезують шляхом окислення диметилсульфоксиду гарячим 30 %-ним розчином пероксиду водню в крижаній оцтовій кислоті. Синтез супроводжується значними втратами пероксиду водню, цільовий продукт підлягає багатоступеневому очищенню. Можливості керованого синтезу диметилсульфону і МСК високої чистоти з‘являються при застосуванні електрохімічного методу окислення диметилсульфоксиду у його водному розчині на мало зношуваному аноді з високою перенапругою кисневої реакції. Можливості такого керованого синтезу є актуальним через здатність сульфуру до легкої зміни ступеня окислення. Дослідження кінетики анодних процесів на платиновому електроді проводили в діапазоні концентрацій 1,0…4,0 моль дм⁻³ диметилсульфоксиду. Підйом струму електролізу спостерігався при потенціалах, що є більш позитивними за 1,3…1,4 В. За таких потенціалів на платиновому аноді, вкритому шаром оксидів платини, відбувається виділення кисню. Для гальмування процесу виділення кисню і досягнення потенціалів утворення пероксидних радикалів у водні розчини диметилсульфоксиду додали сульфатну кислоту у кількості 0,2 моль дм⁻³. Це дозволяє зсунути потенціали підйому струму електролізу у 0,2 моль дм⁻³ Н₂SO₄ до 1,7…1,9 В. Що вказує на процеси утворення пероксидних радикалів на поверхні платинового аноду. При досягненні потенціалів 1,78…1,80 В спостерігається гранична густина анодного струму. Значення граничної густини анодного струму також залежить від концентрації диметилсульфоксиду. Так, для 1,0 моль дм⁻³ диметилсульфоксиду, додаванням 0,2 моль дм⁻³ Н₂SO₄, гранична густина анодного струму складає 32 мА см⁻², а для 4,0 моль дм⁻³ диметилсульфоксиду, додаванням 0,2 моль дм⁻³ Н₂SO₄, –55 мА см⁻². Подальше підвищення концентрації диметилсульфоксиду в електроліті не призводить до збільшення граничної густини анодного струму. Це можна пояснити повним витісненням молекул протонованої води з поверхні платинового аноду і зникненням джерела утворення гідроксильних груп. Подальший зсув анодного потенціалу позитивніше за 2,00…2,05 В призводить до стрімкого зростання густини струму. При таких потенціалах диметилсульфоксид і диметилсульфон окислюються до метансульфонової кислоти з паралельним перебігом процесів виділення кисню і пероксиду водню.
Кінетика анодних процесів при окисленні водних розчинів диметилсульфоксиду
Keywords: platinum electrode; oxygen release; peroxide radicals; ultimate current; платиновий електрод; виділення кисню; пероксидні радикали; гранична густина струму